Neuer Urintest kann Progressionsrisiko bei Knorpelschäden abschätzen (Aktuelle Rheumatologie, 2017)
Poole AR et al. Ability of a Urine Assay of Type II Collagen Cleavage by Collagenases to Detect Early Onset and Progression of Articular Cartilage Degeneration: Results from a Population-based Cohort Study.